2010
DOI: 10.1617/s11527-010-9696-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of asphalt low shear viscosity to predict permanent deformation performance of asphalt concrete

Abstract: The permanent deformation performance of asphalt concrete is strongly dependent on the rheological properties of the asphalt binder. It has been recognized that the asphalt's low shear viscosity (LSV) characterizes the mixture's rutting resistance. At the same time, the pavement temperature is one of the main factors that significantly affect the mixture performance. In this work the rutting performance of mixtures prepared with the same aggregate gradation and different binders [conventional (C), multigrade (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…Thus, low shear LSV viscosity is sometimes suggested to solve this problem. It was also shown that complex viscosity measured at 0.001 and 0.01 Hz give as a good correlation with mixture rutting performance as those measured at 0.0001 Hz [72].…”
Section: Fig 14 Complex Viscosity Versus Frequency [19]mentioning
confidence: 73%
See 4 more Smart Citations
“…Thus, low shear LSV viscosity is sometimes suggested to solve this problem. It was also shown that complex viscosity measured at 0.001 and 0.01 Hz give as a good correlation with mixture rutting performance as those measured at 0.0001 Hz [72].…”
Section: Fig 14 Complex Viscosity Versus Frequency [19]mentioning
confidence: 73%
“…The ZSV concept is based on the fact that the purely dissipative viscous component is solely responsible for the non-recoverable deformation [71]. Zero shear viscosity is strongly related to rutting resistance of bituminous materials and many studies showed that ZSV of binders has a strong correlation to rutting performance [72,73]. The ZSV is highly influenced by the higher molecular weight fraction and binder stiffness, and thus, it can reliably predict the rutting resistance of binders under slow-moving load [72].…”
Section: Zero Shear Viscosity Zsvmentioning
confidence: 99%
See 3 more Smart Citations